2010
DOI: 10.1111/j.1752-1688.2009.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Quality Performance of a Constructed Stormwater Wetland for All Flow Conditions1

Abstract: Wadzuk, Bridget M., Matthew Rea, Gregg Woodruff, Kelly Flynn, and Robert G. Traver, 2010. Water‐Quality Performance of a Constructed Stormwater Wetland for All Flow Conditions. Journal of the American Water Resources Association (JAWRA) 46(2):385‐394. DOI: 10.1111/j.1752‐1688.2009.00408.x Abstract:  Results from a multiyear study demonstrate that a constructed stormwater wetland (CSW) improves urban stormwater runoff quality mitigating downstream impacts. Best management practices, such as CSWs, can comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 19 publications
(31 reference statements)
1
26
1
Order By: Relevance
“…Constructed stormwater wetlands (CSWs) are often advantageous over other BMPs in that they tend to maintain a continuous flow, involving base flow and storm flow whereas other BMPs (retention ponds, etc.) may only be functioning as a treatment mechanism during and post storm events (Wadzuk et al, 2010).…”
Section: Urban Stormwatermanagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructed stormwater wetlands (CSWs) are often advantageous over other BMPs in that they tend to maintain a continuous flow, involving base flow and storm flow whereas other BMPs (retention ponds, etc.) may only be functioning as a treatment mechanism during and post storm events (Wadzuk et al, 2010).…”
Section: Urban Stormwatermanagementmentioning
confidence: 99%
“…Wetland performance in treating stormwater is a function of numerous factors including, but not limited to hydraulic loading rate, detention time, storm intensity, runoff volume, wetland size (Carleton et al, 2001), season (Yousef et al, 1986;Hvited-Jacobsen et al, 1989), maintenance intensity (Hunt & Lord, 2007), and vegetative species and placement (Jenkins & Greenway, 2005). While most studies have shown that stormwater wetlands are effective at reducing nutrient and pathogen influent concentrations, the reported treatment efficiencies are often variable because of the many factors which influence pollutant treatment (Line et al, 2008;Hathaway et al, 2009;Wadzuk et al, 2010 ).…”
Section: Urban Stormwatermanagementmentioning
confidence: 99%
“…Volume reductions in CSWs are typically negligible [8,12,52]; however, some systems have experienced significant reductions (24-55%) due to seepage and evapotranspiration [8,50,53,54]. Consequently, CSW designs based on this model would provide conservative area recommendations, and further refinements to the model could include water balance calculations to evaluate CSW performance and sizing on a mass loading basis.…”
Section: Discussionmentioning
confidence: 99%
“…When assessed from a “triple bottom line” perspective, one that assesses social and environmental benefits in addition to the financial, GI is shown to have significant additional benefits (Wolf, ; Neukrug and Camp, ; Wise et al ., ). GI can complement or replace existing infrastructure, improving functionality or reducing costs (Bedan and Clausen, ; Wadzuk et al ., ; Opperman et al ., ; Steffen et al ., ). GI primarily benefits the environment by eliminating the need for traditional grey infrastructure and its associated environmental impacts.…”
Section: Introductionmentioning
confidence: 99%